Determining Stress and Performance Levels of Academics: A Cross-Sectional Study - Gülşen Ulaş Karaahmetoğlu; Zeynep Arabacı (Association of Nurse Managers, 2023)
Aim: The study aimed to assess stress and performance levels in academics and examine the correlation between their descriptive characteristics with stress and performance levels. Method: We conducted a descriptive study with 315 academics and collected the data via a descriptive survey form, the Stress Evaluation Scale and the Performance Evaluation Scale. Results: The stress scores of the academics were found to be moderate 32.24 (SD=7.26). It was determined that institution-oriented performance scores were 16.99 (SD=2.00), teamwork-oriented performance scores were 21.44 (SD=3.10), and total performance scores were 38.44 (SD=4.61). Conclusion: It was concluded that the increase in academic positions caused a decrease in performance, and that the stress level of academics was higher among those who were young, single, childless, had negative work-related issues, did not eat regularly, had chronic diseases, and used drugs and alcohol regularly.
Keywords: education; stress; RT1-120; academics; Nursing; performance; 4. Education